Crops' Yield and Roots Response to Soil Phosphorus Distribution Resulting From Long-Term Soil and Phosphate Fertilization Management Strategies - Nunes, Rafael de Souza; Sousa, Djalma Martinhão Gomes de; Goedert, Wenceslau J.; de Oliveira, Luiz Eduardo Zancanaro; Pinheiro, Thamires Dutra (Frontiers in Agronomy, 2021)
We investigated labile P and roots distribution in the soil profile and their effect on phosphorus uptake and soybean and corn yield under different tillage systems and phosphate fertilization managements. In a long-term experiment fertilized with triple superphosphate (TSP) or reactive phosphate rock (RPR), where the fertilizer was band-applied in the crop row or broadcasted under conventional tillage (CT) or no-tillage (NT), we evaluated labile P (Bray-1) and root density distribution in depth, and crop yield, biomass production and P uptake by soybean (16th crop) and corn (17th crop). The soil disturbance in CT promoted more homogeneous soil P distribution while in NT there was a strong gradient in depth, with nutrient accumulation in the fertilizer application zone. In general, the average content of P in the 0-20 cm layer was similar for the two soil management systems and for the two application methods, but higher for TSP in relation to RPR. Root distribution of soybeans in NT and corn in both tillage systems showed a strong relationship with soil P distribution. The production of biomass, P uptake and grain yield of soybean in CT was influenced by phosphate fertilization management and generally presented lower performance than in NT, what did not occur for corn possibly due to a better P uptake efficiency compared to that of soybean. Greater stratification on the distribution of soil P and soybean and corn roots in NT did not represent any limitation on the nutrient uptake and yield of these crops, not even in the extreme case where the fertilizer was continuously broadcast on the soil surface. The influence of soil tillage management and phosphate fertilization was more evident in soybeans than corn.